THE ROLE OF PUBLIC-PRIVATE PARTNERSHIPS (PPP) IN OVERCOMING BUDGETARY AND BUREAUCRATIC BARRIERS IN INFRASTRUCTURE DEVELOPMENT IN INDONESIA - Kurdi; Polem, Irfan (Universitas Bengkulu, 2025)
This study aims to analyze the role of Public-Private Partnerships (PPP) in overcoming budgetary and bureaucratic barriers in infrastructure development in Indonesia. Employing a normative juridical research method through statutory and conceptual approaches, this study evaluates the legal framework and implementation of PPPs, including Presidential Regulation No. 38 of 2015 and other supporting regulations. The findings indicate that PPPs represent an innovative alternative solution to address the limitations of state budget (APBN) funding and accelerate the provision of strategic infrastructure through private sector involvement. Moreover, PPPs contribute to streamlining administrative procedures that are often hindered by bureaucratic inefficiencies. Nonetheless, challenges such as regulatory complexity, project readiness, and inter-institutional coordination remain significant obstacles. With regulatory refinement and stronger institutional support, PPPs hold great potential to promote efficient and sustainable infrastructure development in Indonesia. Keywords: PPP; Infrastructure; Budget Constraints; Bureaucracy; Legal Framework